2016
DOI: 10.1371/journal.pone.0150520
|View full text |Cite
|
Sign up to set email alerts
|

Past Human Disturbance Effects upon Biodiversity are Greatest in the Canopy; A Case Study on Rainforest Butterflies

Abstract: A key part of tropical forest spatial complexity is the vertical stratification of biodiversity, with widely differing communities found in higher rainforest strata compared to terrestrial levels. Despite this, our understanding of how human disturbance may differentially affect biodiversity across vertical strata of tropical forests has been slow to develop. For the first time, how the patterns of current biodiversity vary between three vertical strata within a single forest, subject to three different types … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 53 publications
0
32
0
Order By: Relevance
“…), with canopy assemblages showing a higher susceptibility to decline in disturbed forest or logged forest than those found at ground level (Dumbrell & Hill , Whitworth et al . ). Since we used transect surveys focussed on ground level species, canopy species are likely to be under‐represented in our results.…”
Section: Discussionmentioning
confidence: 97%
“…), with canopy assemblages showing a higher susceptibility to decline in disturbed forest or logged forest than those found at ground level (Dumbrell & Hill , Whitworth et al . ). Since we used transect surveys focussed on ground level species, canopy species are likely to be under‐represented in our results.…”
Section: Discussionmentioning
confidence: 97%
“…In addition to soil factors, the distribution of plant communities might be related to the specific geographical location providing unique habitats (Wassen, Peeters, and Venterink 2002;Dwirek, Kauffman, and Baham 2006;Mellado and Zamora 2015;Oliveira, Torezan, and Cunha 2015;Zellweger et al 2015;Whitworth et al 2016). The plant communities in the study area were divided into seven types, which had substantial differences in their growth requirements.…”
Section: Relationship Between Vegetation and Soil Factorsmentioning
confidence: 99%
“…This can consequently facilitate increased awareness about the biodiversity and conservation value of both primary and regenerating tropical forests [58]. Understanding the effects of anthropogenic disturbance to canopy environments is particularly important given that a number of different taxonomic assessments have suggested that biodiversity within canopy strata is under greatest threat due to habitat modification [4,[7][8][9][10][11]59]. Here we suggest that the arboreal camera trapping method can be both useful and cost-effective in the long term for conservation assessments and can provide opportunities to learn more about some of the most charismatic [12] and threatened species in the world [38,39,54] which may otherwise remain largely unknown and could quietly disappear from our planet.…”
Section: Implications For Conservationmentioning
confidence: 99%